Karakter Antroposentrisme Kapitalis terhadap Alam dan Perempuan Lembah Baliem - Rahmat Prayogi (Edukasi Lingua Sastra, 2019)
This research was conducted to investigate capitalistic anthropocentrism towards nature and women in the novel Tanah Tabu. Freeport is an actor of capitalistic anthropocentrism while the Baliem Valley and the character of women in Tanah Tabu are representatives of the exploited objects. The analysis was carried out using the ecofeminism theory by Vandana Shiva. Therefore, the implication was to study the capitalistic anthropocentrism actions of Freeport which were examined based on the objectives of western colonialism (the United States) that came to Papua by developing the mining industry. The results of this study are first, the character of capitalistic anthropocentrism by Freeport is known from their motives in developing civilization with modern science, modernism towards conservatism, and colonialism. Second, ecofeminism places the character of Tanah Tabu women in role dualism; as victims and fighters against capitalistic anthropocentrism.